2019
DOI: 10.3389/fimmu.2019.00674
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification for a Model of Neonatal Fc Receptor-Mediated Recycling of Endogenous Immunoglobulin G in Humans

Abstract: Salvage of endogenous immunoglobulin G (IgG) by the neonatal Fc receptor (FcRn) is implicated in many clinical areas, including therapeutic monoclonal antibody kinetics, patient monitoring in IgG multiple myeloma, and antibody-mediated transplant rejection. There is a clear clinical need for a fully parameterized model of FcRn-mediated recycling of endogenous IgG to allow for predictive modeling, with the potential for optimizing therapeutic regimens for better patient outcomes. In this paper we study a mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Based on the initial estimates, including experimentally measured rates of FcRn‐mediated recycling (internalization, degradation, and recycling), 27 PK parameters were either fixed or further fitted to the mean ALX‐148 concentration and CD47 occupancy measured in the phase I clinical trial. 33 Seven parameters were fitted to PK data (population mean) on four dose levels simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the initial estimates, including experimentally measured rates of FcRn‐mediated recycling (internalization, degradation, and recycling), 27 PK parameters were either fixed or further fitted to the mean ALX‐148 concentration and CD47 occupancy measured in the phase I clinical trial. 33 Seven parameters were fitted to PK data (population mean) on four dose levels simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the population PK analyses of ALX‐148 showed that ALX‐148 exhibited nonlinear clearance and interacted with neonatal Fc receptors (FcRn) without triggering Fc‐gamma receptor (FcγR)‐mediated effector activity 25 . Therefore, target‐mediated drug disposition (TMDD) 26 via binding with CD47 on red blood cells (RBCs) in the central compartment, and neonatal Fc receptor‐mediated recycling 27 were incorporated into the PK module for ALX‐148. Equations 1–10 describe the dynamics of ALX‐148 (i.e., ][aCD47$$ \left[\mathrm{aCD}47\right] $$), CD47, and FcRn.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More enhanced induction and maintenance immunosuppression is also used and future protocols may utilise novel therapies such as Imlifidase 15 , 16 or neonatal FcR inhibition. 17 If desensitisation is successful and transplantation proceeds, recipients still may have an increased risk of severe post-operative AMR (which could be as early as within 14 days post transplantation), bleeding and mortality. 18 , 19 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…Being a data driven approach, the profile likelihood based method has the advantage of not imposing any restrictions on the algebraic form of the model (Raue et al, 2014). Due to this, the profile likelihood approach has been widely used in systems biology (Gross & Blüthgen, 2020;Lee et al;Coulibaly et al, 2019;Kendrick et al, 2019) wherein the large biological networks lead to complex mathematical models which cannot be assessed via analytical methods. Recently, this approach has seen use in studying identifiability of large scale or complex models for (bio)chemical processes like a lithium-ion battery (Zhou et al, 2020), and the fluidized bed agglomeration process (Golovin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%